Learning strategies for teacher education in the era of globalization - Hashim, Rosnani (2013)
Teachers have been regarded as the “sage” on the stage in the past. They seem to hold the repertoire of knowledge, values and skills to be handed down to the younger generation. In a sense they are like little repositories of knowledge for the civilization. Today with the invention of the computer and information and communication technologies, the repositorical role of the teacher no longer holds true and thus, he or she is no longer the “sage”. The clear demarcation of the teacher and the learner to describe the teachers and students has become blurred due to the advanced ICT technologies which are able to store a large amount of information that can be accessed by students and also teachers. The paper examines the effects of globalization in education and identifies eight shifts in learning strategies that arose from these technologies that will reform teaching strategies accordingly in the new millennium. Teacher Education Programmes need to be aware of these and review their curricula in order to stay relevant. Most important among these new strategies are “teachers as learners and learners as teachers” and learner-centred learning and constructing their own knowledge instead of just being passive learners. (197 words)